Ferroptosis, Necroptosis, and Pyroptosis in Gastrointestinal Cancers: The Chief Culprits of Tumor Progression and Drug Resistance - Zhu, Xudong; Li, Shenglong (Advanced science, 2023)
In recent years, the incidence of gastrointestinal cancers is increasing, particularly in the younger population. Effective treatment is crucial for improving patients’ survival outcomes. Programmed cell death, regulated by various genes, plays a fundamental role in the growth and development of organisms. It is also critical for maintaining tissue and organ homeostasis and takes part in multiple pathological processes. In addition to apoptosis, there are other types of programmed cell death, such as ferroptosis, necroptosis, and pyroptosis, which can induce severe inflammatory responses. Notably, besides apoptosis, ferroptosis, necroptosis, and pyroptosis also contribute to the occurrence and development of gastrointestinal cancers. This review aims to provide a comprehensive summary on the biological roles and molecular mechanisms of ferroptosis, necroptosis, and pyroptosis, as well as their regulators in gastrointestinal cancers and hope to open up new paths for tumor targeted therapy in the near future.